2016
DOI: 10.1007/s10796-016-9723-1
|View full text |Cite
|
Sign up to set email alerts
|

Project description and crowdfunding success: an exploratory study

Abstract: Existing research on antecedent of funding success mainly focuses on basic project properties such as funding goal, duration, and project category. In this study, we view the process by which project owners raise funds from backers as a persuasion process through project descriptions. Guided by the unimodel theory of persuasion, this study identifies three exemplary antecedents (length, readability, and tone) from the content of project descriptions and two antecedents (past experience and past expertise) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
138
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 31 publications
11
138
0
2
Order By: Relevance
“…Indeed, much of crowdsourcing has a prominent monetary dimension that is typically missing in citizen science. For example, turning to crowds for project funding or product developmentcrowdfundingspecifically pursues monetary goals (Choy and Schlagwein 2016;Zhou et al 2018). Likewise, Amazon's Mechanical Turk and CrowdFlower.com serve as intermediaries between companies and online workers (Chittilappilly et al 2016; (Abbasi et al 2018, Kane et al 2014, Kapoor et al 2018, Miranda et al 2016 Social networks, chats, message boards, forums, photo and video sharing apps and platforms Crowdsourcing A model of labour in which an organization turns to crowds (i.e., ill-defined members of the general public) to obtain desired data, goods, or services (Brabham 2013, Ghezzi et al 2017, McAfee and Brynjolfsson 2017, Poblet et al 2017, Zhao and Zhu 2014 Many business, public and even individual initiatives, such as crowdfunding, ideation, contest, citizen science, crisis management or online employment platforms…”
Section: Situating Citizen Science In the Broader Ugc Landscapementioning
confidence: 99%
“…Indeed, much of crowdsourcing has a prominent monetary dimension that is typically missing in citizen science. For example, turning to crowds for project funding or product developmentcrowdfundingspecifically pursues monetary goals (Choy and Schlagwein 2016;Zhou et al 2018). Likewise, Amazon's Mechanical Turk and CrowdFlower.com serve as intermediaries between companies and online workers (Chittilappilly et al 2016; (Abbasi et al 2018, Kane et al 2014, Kapoor et al 2018, Miranda et al 2016 Social networks, chats, message boards, forums, photo and video sharing apps and platforms Crowdsourcing A model of labour in which an organization turns to crowds (i.e., ill-defined members of the general public) to obtain desired data, goods, or services (Brabham 2013, Ghezzi et al 2017, McAfee and Brynjolfsson 2017, Poblet et al 2017, Zhao and Zhu 2014 Many business, public and even individual initiatives, such as crowdfunding, ideation, contest, citizen science, crisis management or online employment platforms…”
Section: Situating Citizen Science In the Broader Ugc Landscapementioning
confidence: 99%
“…Displaying the number of previous business ventures on the platform is a symptom of the reliability of the entrepreneur's background and could enhance trust among potential investors compared to entrepreneurs who have not been active before. Previous research found that founders with a high number of successful project campaigns are more successful in subsequent projects (Courtney et al 2017;Zhou et al 2018;Janku and Kucerova 2018;Siering 2015, 2019).…”
Section: Barriersmentioning
confidence: 99%
“…There was a strong correlation between a project's early promotional activities and the final outcomes. Additionally, project creators' backing history (Zvilichovsky, Inbar, and Barzilay 2013) and project description (Zhou et al 2018) were also effective for improving the prediction accuracy.…”
Section: Crowdfundingmentioning
confidence: 99%